2020
DOI: 10.4314/ovj.v9i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing alternatives to canine rectal thermometry at the axillary, auricular and ocular locations

Abstract: Body temperature is an important component in the diagnosis and treatment of disease in canines. The rectal temperature remains the standard of obtaining temperature within the clinical setting, but there are many drawbacks with this method, including time, access, animal stress, and safety concerns. Interest in using infrared thermometry in canines to obtain body temperature has grown as animal scientists and veterinarians search for non-invasive and non-contact methods and locations of obtaining canine tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Currently, rectal temperature (RT) measurement is the gold standard in conscious veterinary patients. 1 RT in these animals correlates well with the core body temperature as measured via more invasive techniques (ie, esophageal temperature and pulmonary arterial temperature). 2 However, rectal thermometry has several disadvantages, including contribution to patient stress, potential for patient injury, and prolonged time for measurement compared to alternative non-invasive measures, such as aural or corneal temperature.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Currently, rectal temperature (RT) measurement is the gold standard in conscious veterinary patients. 1 RT in these animals correlates well with the core body temperature as measured via more invasive techniques (ie, esophageal temperature and pulmonary arterial temperature). 2 However, rectal thermometry has several disadvantages, including contribution to patient stress, potential for patient injury, and prolonged time for measurement compared to alternative non-invasive measures, such as aural or corneal temperature.…”
Section: Introductionmentioning
confidence: 60%
“… 13 In veterinary medicine, the use of rectal thermometers is also considered the gold standard for routine temperature measurement, likely because of their reported accuracy when compared to core temperature. 1 As in humans, the use of a less invasive technique to obtain body temperature in canine patients, especially in an emergency setting, is alluring. The current study demonstrated that while rectal and AT measurements were similar in normothermic dogs, ATs were significantly different from RTs in hypothermic and hyperthermic patients presenting to the ER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature is one of the vital assessments used to objectively examine a veterinary patient, the results of which can have significant implications for the health status of that patient [ 1 , 2 , 3 ]. Predictive rectal thermometry is the most common form of thermometry used in veterinary clinical practice, despite 30 years of research on alternative modalities [ 4 , 5 , 6 ]. Research on alternatives to rectal thermometry has primarily focused on correlating the temperature values of these alternative methods to either rectal temperatures or a core body temperature [ 4 , 5 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Predictive rectal thermometry is the most common form of thermometry used in veterinary clinical practice, despite 30 years of research on alternative modalities [ 4 , 5 , 6 ]. Research on alternatives to rectal thermometry has primarily focused on correlating the temperature values of these alternative methods to either rectal temperatures or a core body temperature [ 4 , 5 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%